Pengaruh Kompetensi Sumber Daya Manusia, Pemanfaatan Teknologi Informasi, Tingkat Pendidikan, Pengalaman Kerja Dan Pelatihan Terhadap Kualitas Laporan Keuangan (SKPD Provinsi Lampung) - Octavia, Dika; Puspita, Indah Lia; Lukman, Iing (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2021)
This Study Aims To Determine The Effect Of Human Resource Competence, Use Of InformationTechnology, Level Of Education, Work Experience And Training On The Quality Of Financial Reports(SKPD Lampung Province). The Data Collection Method Used PrimaryData, The Population Of ThisStudy Were 4000 Employees From 20 SKPD Lampung Province, Which Consisted Of 100Respondents As The Sample.Based On The Results Of Data Management Using The Multiple Linear Regression Method With SPSSSoftware, It Is Proven That Human Resource Competency, Information Technology Utilization,Education Levels Have A Significant Effect On The Quality Of Financial Statements, But The WorkExperience And Training Variables Have No Effect On The Quality Of Financial Statements.Keywords:Human Resource Competence, Utilization Of Information Technology, Level Of Education,Work Experience And Training.